Playing Pokemon Go: Increased Life Satisfaction Through More (Positive) Social Interactions - Wingenbach, Tanja S. H.; Zana, Yossi (Frontiers in Sports and Active Living, 2022)
Pokemon Go (PoGo) is a social mobile game requiring both physical activity and social interaction, and previous research has reported positive effects of PoGo on physical health. However, little research has been conducted on the effects of PoGo on social functioning and life satisfaction, which are important factors for good mental health. The current study investigated the effects of PoGo on life satisfaction and social functioning in participants with and without self-reported diagnoses of mental disorders. Participants were 434 current PoGo players aged 18–69 of diverse genders and nationalities, with a subsample (N = 138) self-reporting diagnoses of various mental disorders with impairments in social functioning. Participants provided retrospective and current self-report measures about their PoGo use, life satisfaction, social functioning (sociality and social ability) and clinical symptom severity. Results showed higher self-reported social functioning and life satisfaction since playing PoGo compared to the time period before playing, which involved a shift from negative to positive ratings. The increases in self-reported life satisfaction and sociality (but not social ability) were more pronounced for the clinical compared to the non-clinical subsample. Results also showed the effect of the social ability change on the life satisfaction change was mediated by the sociality change and moderated by the number of daily in-person player interactions (including strangers). The findings here, using subjective judgements, show that PoGo motivates social interactions and increases life satisfaction, demonstrating that social mobile gaming provides an easy to implement tool to subjectively improve social functioning. This has important implications for populations with social difficulties and reduced social motivation.